Adrenal incidentaloma (AI) - a puzzle not only for endocrinologists - Dubaj, Maciej; Dembowska, Aleksandra; Bigosiński, Karol (Journal of Education, Health and Sport, 2022)
An adrenal incidentaloma (AI) is any lesion ≥ 1 cm in diameter detected during radiological diagnostics unrelated to suspected adrenal pathology. Each case of an AI requires extended hormonal and imaging assessments to accurately determine the nature of the tumor and its hormonal activity. The frequency of this tumor’s diagnostics has increased exponentially due to the continuous progress in the development of imaging methods, especially computed tomography and magnetic resonance imaging. The most common etiology of AIs are hormonally inactive adenomas of the adrenal cortex, but there are also adrenal cortex carAIcinomas, phaeochromocytoma, metastatic or infectious lesions. In the case of confirmation of the type of lesion, the management involves adrenalectomy or a sufficiently long clinical observation. In recent years, new markers of the malignancy of AI tumors have been discovered, both in imaging and biochemical diagnostics, which is associated with improvements in the accuracy of diagnosis and patient management. The aim of this study was to describe the definition, etiology and epidemiology of AIs and to draw attention to the complexity of diagnostics and therapy of accidentally diagnosed adrenal tumors. Current publications and guidelines from scientific societies around the world were reviewed, using keywords that were compatible with MeSH.